Investigations on Material and Mechanical Properties, Air‐Permeation Behavior and Filtration Performance of Mullite‐Bonded Porous SiC Ceramics. Issue 5 (28th May 2013) - Dey, Atanu; Kayal, Nijhuma; Chakrabarti, Omprakash; Caldato, Rafael Falchi; Innocentini, Murilo Daniel de Mello; Guerra, Vadila Giovana
<x xml:space="preserve">Abstract</x> A theoretical relation between processing parameters and porosity (29–56%) of mullite‐bonded porous SiC ceramics was derived and validated with experimental data. Porosity‐dependent variation of fracture strength (9–34 MPa) and elastic modulus (7–28 GPa) was explained by the minimum solid area model. At room temperature, the Darcian, k1 (1.2 × 10−13–1.6 × 10−12 m2) and the non‐Darcian, k2 (4.6 × 10−9–2.7 × 10−7 m) permeability coefficients showed linear variation with porosity. Tests conducted up to 650°C indicated an increase in k1 with temperature and a reverse trend for k2. Airborne NaCl nanoparticle filtration tests showed good performance of SiC ceramics with fractional collection efficiency of >99% at 46–56% porosity levels.